Author correction: the copy number variation landscape of congenital anomalies of the kidney and urinary tract - Verbitsky, Miguel; Lozanovski, Vladimir J. (Nature genetics, 2019)
In the version of this article initially published, affiliation 38 incorrectly read “ICNU-Nephrology and Urology Department, Barcelona, Spain”; “Renal Division, Hospital Clinic, IDIBAPS, University of Barcelona, Barcelona, Spain” is the correct affiliation. The error has been corrected in the HTML and PDF versions of the article.
Gesehen am 10.07.2019